Latest advances in atomic cluster collisions : structure and dynamics from the nuclear to the biological scale - International Symposium "Atomic Cluster Collisions: Structure and Dynamics from the Nuclear to the Biologial Scale (2007 : Darmstadt, Germany); Connerade, Jean-Patrick; Solov'yov, Andrey V. (London : Imperial College Press, 2008)
40